Three-dimensional printed realistic pediatric static and dynamic airway models for bronchoscopy and foreign body removal training - Maier, Pia; Silvestro, Elizabeth; Goldfarb, Samuel B.; Piccione, Joseph; Phinizy, Pelton A.; Andronikou, Savvas (Pediatric pulmonology, 2021)
For mastering bronchoscope handling, positioning, and directing of the bronchoscope in response to the intraluminal view provided by the bronchoscope camera, sufficient training is necessary, especially in infants and toddlers who have smaller airways, faster respiratory rates, and higher airway collapsibility. With the use of three-dimensional printing, we aimed to develop a set of anatomically accurate and low-cost airway models for teaching and training of bronchoscopy technique and foreign body removal: a translucent airway box model, a static airway model, and a dynamic airway model consisting of a flexible tree model connected to a pump that allows simulation of airway collapsibility during breathing. Computed tomography (CT) patient data of three different ages (1, 5, and 18 years of age) was imported into Materialise Mimics, segmented, and printed using VisoClear and soft Tango+ material. The models were evaluated by three pediatric pulmonology attendings for anatomical accuracy and usefulness for teaching and training. The translucent airway box model was preferred for the initial presentation of bronchoscope handling and learning anatomy in three dimensions. The static and flexible tree models were used to train bronchoscope handling and foreign body removal. The dynamic model provided the most realistic representation of a pediatric airway throughout the respiratory cycle with increased patency during inspiration and relative collapse during exhalation. Objective verification of anatomical accuracy and physiology of breathing motion was obtained by comparing CT scans of the model with original images and by application of 4D dynamic CT airway imaging protocols, respectively.
Gesehen am 18.08.2023